1972
DOI: 10.1111/j.1532-5415.1972.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine in Geriatric Psychiatry

Abstract: Fifty patients in the psycho-geriatric unit of a county hospital were divided randomly into two groups; 30 were treated with chlorpromazine for six weeks, and 20 constituted the controls. The morning blood pressure (with the patient in the standing position) was used to monitor chlorpromazine dosage; the highest dosage reached was 200 mg daily (5 cases), but in 11 cases the dosage could be only 50 mg daily. Improvement was assessed by means of Rating Scales (NOSIE and BPRS) and Global Assessment. Chloral hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…A total of 33 studies were identified in which neuroleptic medications were compared to placebo or to other medications in geriatric samples that comprised some dementia patients 12–44 . In studies intended to compare several medication classes in parallel groups, only neuroleptic and placebo data were used for the metaanalyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 33 studies were identified in which neuroleptic medications were compared to placebo or to other medications in geriatric samples that comprised some dementia patients 12–44 . In studies intended to compare several medication classes in parallel groups, only neuroleptic and placebo data were used for the metaanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Studies Comparing Neuroleptics with Placebo Of the 17 placebo‐controlled studies identified, 12–28 13 used parallel groups and four used cross‐over designs. Eight of the 14 double‐blind studies used random treatment assignment, and one used “preassignment” to treatment (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroleptic medications have become the mainstay in the treatment of agitation in the elderly demented patient 14 . Uncontrolled studies and case reports have claimed that low doses of neuroleptics produce dramatic improvement in a wide variety of behavioral disturbances in geriatric patients residing in nursing homes or in state hospitals 15–25 . However, the majority of these claims are difficult to substantiate because they were based primarily on impressionistic outcome measures in populations that often included patients with functional psychiatric disorders.…”
Section: Neurolepticsmentioning
confidence: 99%
“…However, another study (Auchus and BisseyBlack, 1997) found that 3 mg/d of haloperidol was no more effective than placebo in reducing agitation, but was associated with much greater toxicity. Likewise, one study has reported a slight improvement with chlorpromazine (Birkett and Boltuch, 1972), but several studies indicate a rate of deterioration that is similar to or higher than that seen among patients receiving placebo (Robinson, 1959;Birkett and Boltuch, 1972) Results with thioridazine have also been inconsistent. A six-week study (Phanjoo and Link, 1990) involving nine patients taking 50± 200 mg demonstrated a signi®cant reduction of patients' BPRS total scores from 24 to 7, although only one patient was rated as`very much improved' on the CGI-S. By contrast, an eight-week study (Barnes et al, 1982) found that thioridazine was no better than placebo on any item of the BPRS or on the Sandoz Clinical Assessment±Geriatric scale, but this may have been due to the use of a 25-mg/d dose, which may have been inadequate.…”
Section: Discussionmentioning
confidence: 99%